Probing the Atmospheric Precipitable Water Vapor with SOFIA. II. Atmospheric Models from ECMWF. (13th April 2021) - Iserlohe, C.; Fischer, C.; Vacca, W. D.; Fischer, N.; Colditz, S.; Krabbe, A.
Abstract: SOFIA is an airborne observatory for far-infrared astronomy. Although SOFIA flies at altitudes of ∼41, 000 feet, any far-infrared observations from within the Earth's atmosphere are nevertheless hampered by water vapor absorbing the astronomical signal. The atmospheric parameter governing absorption is the total upward precipitable water vapor, PWV. In this paper we investigated if data of the Earth's atmosphere provided by the European Centre for Medium-Range Weather Forecasts, ECMWF, can be used to determine spatially and time-resolved PWV data to allow a more precise calibration of far-infrared data taken with SOFIA along its flight path. We found that PWV values obtained from ECMWF correlate extremely well with independently determined PWV values obtained with the FIFI-LS instrument onboard SOFIA. We determined maximum observing time intervals (depending on the pressure altitude SOFIA is flying at) within which the upward PWV value changes inflight by less than a certain amount. We also present a new calibration method which enhances data quality and observing efficiency with FIFI-LS significantly. Furthermore our new method is universal and may be applied to data from all of SOFIA's instruments.